Study on Effectiveness of School Leaders in Primary Schools of Wolaita and Dawuro Zones in Southern Region of Ethiopia - Kebede, Deribe Debella; Demissie, Endale Berhanu; Labiso, Tafano Ouke (Advances in Social Sciences Research Journal, 2019)
Effective school leader is an educational leader who promotes the success of all students by facilitating the development, expression, implementation, and stewardship of a vision of learning that is shared and supported by the school community. In light of this, this research was aimed at assessing the effectiveness of school leadership in primary schools of Wolaita and Dawuro Zones. To conduct the study a descriptive survey method was used. Samples of 7 woredas, 28 schools, 28 school leaders, 28 supervisors, 28 parent representatives, 140 teachers and 280 students were selected by simple random and purposive sampling techniques as data sources. To answer the basic questions, data were collected from groups of sample respondents through questionnaires, interview and document analysis. The data were analyzed using descriptive statistical techniques including means grand means and percentages. The results of the study revealed that the school leaders were effective in managing non instructional activities which were also reflected in teachers’ performance. Moreover, leaders’ effectiveness in enhancing students learning was found to be medium. Thus the organization of cluster training centers, in service training, experience sharing and focus on instructional tasks in planning documents are among recommendations. Key Terms: Effectiveness, Leadership, Educational leadership, Performance, Primary Schools